Case Report: Clinical impact of BRCA1 and BRIP1 vs. BRCA1 and BRCA2 germline double heterozygosity in ovarian cancer: a comparative case study - Zheng, Limei; Zhu, Qianyuan; Zhang, Fenglan; Qiu, Hao; Qin, Lan; Yang, Jianhua; Qi, Ming (Frontiers in Oncology, 2025)
Ovarian cancer (OC) is a highly heterogeneous malignancy influenced by germline genetic factors, with BRCA1/2 mutations being well-established risk factors. Germline double heterozygosity (GDH), particularly involving rare combinations, remains poorly understood. This study presents the first report of BRCA1/BRIP1 GDH in a case of Chinese OC patients and compares their clinical characteristics and treatment responses to a patient with BRCA1/BRCA2 GDH. The BRCA1/BRIP1 GDH patient is a 46-year-old female diagnosed with advanced ovarian adenocarcinoma at clinical stage FIGO IVB, exhibited severe chemotherapy-induced toxicity and postoperative complications, including chylous leakage. In contrast, the BRCA1/BRCA2 GDH patient is a 44-year-old female with high-grade serous ovarian cancer at clinical stage FIGO IIIC, tolerated chemotherapy well. Both patients experienced clinical benefit from Olaparib maintenance therapy. Genetic testing confirmed pathogenic variants in both cases, revealing distinct clinical trajectories influenced by different GDH profiles. Our findings suggest that different GDH combinations may influence chemotherapy tolerance and therapeutic effectiveness in OC. BRCA1/BRIP1 GDH patients may require personalized dose adjustments to mitigate toxicity and optimize efficacy. This study underscores the clinical significance of GDH heterogeneity and the importance of comprehensive genetic testing for guiding individualized treatment strategies. Future research should focus on expanding sample sizes and conducting in-depth functional analyses to further clarify the clinical implications of different GDH types, ultimately refining treatment approaches for GDH-associated OC.